ln(x)+ln(x+6)=7

Simple and best practice solution for ln(x)+ln(x+6)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x)+ln(x+6)=7 equation:


Simplifying
ln(x) + ln(x + 6) = 7

Multiply ln * x
lnx + ln(x + 6) = 7

Reorder the terms:
lnx + ln(6 + x) = 7
lnx + (6 * ln + x * ln) = 7
lnx + (6ln + lnx) = 7

Reorder the terms:
6ln + lnx + lnx = 7

Combine like terms: lnx + lnx = 2lnx
6ln + 2lnx = 7

Solving
6ln + 2lnx = 7

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-7 + 6ln + 2lnx = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + 6ln + 2lnx = 0

The solution to this equation could not be determined.

See similar equations:

| -4y=40 | | 2a^3-2a^2-84a=0 | | 5w-4=16-5w | | 6(x-9)-(x+12)= | | 4x-2(2x)=0 | | 3.2+0.8= | | 9-y=7 | | -2g(-6-4g)= | | -3m=0.923076 | | 2x-2(2x-8)=3(2x-7)+7x | | 10=6x-26 | | 10x+2=4x+1+27 | | 3y-30=10-y | | 10-1.3b=-2 | | -1y+4=-1 | | 7x-3=5(x-2) | | 15x+12X+45=180 | | Y=6.5x | | -(n^2+3n-1)= | | t-5t+4= | | 7x+7(5x+37)=-35 | | 3a-8a=5 | | 0.571429x=16 | | 5x-2(2x-7)=3(2x-8)+7x | | x^2+y^2=53 | | (3n-4)9= | | 4+3n=n+40 | | (3+x)(3+x)=160 | | 3(2c-4)-4=2c+4 | | x^2+6x-151=0 | | N=6.10n-15 | | y=2x^4-15x^3+18x^2 |

Equations solver categories